The policy implementation process in the upper secondary education system (senior cycle) and videregaende skolen in science and mathematics in the Republic of Ireland and the Kingdom of Norway from 1960 - 2005 - Mooney Simmie, Geraldine (Trinity College (Dublin, Ireland). School of Education, 2009)
The substantive issue at the heart of this thesis is identifying the key changes in science and mathematics mandated by the state, in upper secondary academic education, and seeing the extent to which these are translated into school praxis, through the perspectives of management and teachers and, of equal importance, through the organisational and structural reforms taking place at the level of the school. The reform process is regarded as a complex social phenomenon and like all top-down educational change has a history of being robustly resisted at the school site.
Keywords: Education, Ph.D.; Ph.D. Trinity College Dublin.